A Warrior Society: Data From 30 Countries Show That Belief in a Zero-Sum Game Is Related to Military Expenditure and Low Civil Liberties - Różycka-Tran, Joanna; Jurek, Paweł; Olech, Michał; Piotrowski, Jarosław; Żemojtel-Piotrowska, Magdalena (Frontiers in Psychology, 2019)
The aim of this paper was to investigate the relationship between a perceived antagonistic view of social relations (as a struggle for limited resources), measured by the Belief in a Zero-Sum Game (BZSG) Scale, national military expenditure, and civil liberties. We used multi-level modeling to analyze data on 5,520 participants from 30 countries, testing the hypothesis that a country's level of militarization and civil liberties would be associated with its people's belief in a zero-sum game. We hypothesized that BZSG is more typical of countries that try to gain more resources or defend their interests and thus have high military expenditure but low civil liberties. The results confirmed the stated hypothesis and showed that a country’s high military expenditure and low level of civil liberties correlates positively with citizens’ BZSG. The use of multi-level modeling to account for within- and across-country variation is a main contribution of the study. In conclusion, the reported triad of individual beliefs, military expenditure, and civil liberties seems to be beneficial in linking individual-level data with national-level indices that have major importance for the wellbeing of the world.